AISI D2 punch head damage: Fatigue and wear mechanism. (November 2021) - Zeidi, Abdelwaheb.; Ben Saada, Fatma.; Elleuch, Khaled.; Atapek, Hakan.
Highlights: Punch head AISI D2 damage was investigated in order to achieve causes failure when punching a plettac. SEM observations showed gun drill fatigue and chromium carbides cracking in AISI D2 steel. Punch head expansion, brinelling and cracking were the main causes leading to failure. High punching force, plastic deformation of the punch and back up plate wear were also behind tool damage. Heat treatment, head punch design then tool guiding solution (gun drill) have to be improved. Abstract: The purpose of this work is to analyze the damage of AISI D2 punch head whose main part is used halting production. The punch head failure could be categorized into three major types namely the swollen, the mated and the cracked punch. Furthermore, this study underlines the punch damage causes using the optical microscope and SEM so as to check and characterize the microstructure of cracks. In this respect, EDS was used to inspect corrosion, then XRD and micro hardness were utilized to identify the chromium carbides. The obtained results showed that back up plate wear and fatigue, low toughness of AISI D2 steel, poor heat treatment as well as non-optimized punch-gun drill clearance are the main causes for tool premature damage. For the sake of analyzing its microstructure, AISI D2 Punch head damage was extensively investigated in this work using various methods such as SEM. Additionally, EDS micrography, Xray diffraction and micro hardness were exploited to make comparison between the damaged tools. To this effect, we were able to distinguish between three types of damaged punches namely the swollen, the mated and the cracked one. Concerning the mechanical fatigue, low wear resistance as well as weak toughness proved to be behind the short tool life. Poor heat treatment and non-optimized punch-gun drill clearance can also lead to tool premature damage. Therefore, a suitable head punch design, an optimized clearance and a new punch guiding solution are indispensable to improve the punching conditions.